1981
DOI: 10.1007/bf02774464
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-ulcer drugs on the recovery of gastric mucosal glycoproteins with aspirin-induced gastric damage in rat

Abstract: The efficacy of two anti-ulcer drugs, Cimetidine and Cetraxate, on the mucus glycoproteins of gastric mucosa in the aspirin-induced gastric damage was studied in rats. Simultaneous or previous oral administration of Cimetidine or Cetraxate with aspirin reduced the diminution of the mucus glycoproteins which was occurred by aspirin administration. The recovery of the content of mucus glycoprotein in drug dosed rats occurred within 3 h after aspirin dosing and was nearly 90% of control at 5 h in all cases. Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…They also demonstrated that mucosal glycoprotein content remained low after the macroscopic lesions had naturally diminished 9 hr after aspirin treatment (20). Moreover, the mucosal lesion formation in our study (shown in Table 2) is much more severe than that reported by Azuumi et al (20,28). Therefore, it is pre sumed that cimetidine could hardly restore the biochemical function (i.e., glycoprotein synth esis) in the gastric mucosa under such severe experimental conditions as in the present study, even though it could inhibit the macro scopic lesion formation.…”
Section: Discussionsupporting
confidence: 62%
“…They also demonstrated that mucosal glycoprotein content remained low after the macroscopic lesions had naturally diminished 9 hr after aspirin treatment (20). Moreover, the mucosal lesion formation in our study (shown in Table 2) is much more severe than that reported by Azuumi et al (20,28). Therefore, it is pre sumed that cimetidine could hardly restore the biochemical function (i.e., glycoprotein synth esis) in the gastric mucosa under such severe experimental conditions as in the present study, even though it could inhibit the macro scopic lesion formation.…”
Section: Discussionsupporting
confidence: 62%
“…The present authors have developed a convenient method for achieving these ob jectives. Using this method, quantitative and qualitative changes in mucus glycoproteins in gastric mucosa during the pathological [12][13][14], physiologic [15] and pharmaceutical [22] changes of the stomach have been obtained. In the present study, treatment with prosta glandin derivatives was found not to signifi cantly change mucosal mucus glycoprotein content either in corpus or antrum.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that they act by inhibiting secretion of gastric acid and thus preventing the gastric mucosal barrier damage produced by HC1 [2]. On the other hand, a number of investigators are in agreement that cimetidine, apart from the above-mentioned mode of action, increases the production of gastric mucosal glycoproteins [1,7,11,12]. In a recent study dealing with the protective role of famotidine on aspirin-induced gastric mucosal lesions, electron microscopic observations revealed an increase in both the mucous granules and Golgi apparatus -where mucus is manufactured -within the surface epithelial cells in rats pretreated with famotidine [4].…”
Section: Introductionmentioning
confidence: 69%